"Green Growth" : An Exploratory Review - Toman, Michael (World Bank, Washington, DC, 2012)
The concept of "Green Growth" is a focus of much interest and considerable debate among decision makers concerned with enhancing both nearer-term economic progress and longer-term environmental sustainability. Proponents of Green Growth emphasize not only the need to protect various forms of natural capital to sustain improvements in material living standards and poverty reduction, but also the potential for strategically crafted environmental policies to achieve sustainability at low cost, perhaps even to help stimulate growth. However, there has been so far relatively little exploration of the analytical underpinnings of Green Growth, or its ambiguities. An exploratory investigation of the goals and underlying assumptions embedded in various conceptions of Green Growth facilitates consideration of how they might be interpreted vis-à-vis standard principles of intertemporal economic efficiency, including the value of the environment. Several plausible potential channels are identified for how synergy between economic growth and environmental sustainability might be more extensive than implied by standard economic theory. However, it is not possible to address their practical significance without more empirical research than is currently available. Consequently, some claims of substantial win-win opportunities between growth and the environment may be premature.